Double-pass Mach–Zehnder fiber interferometer pH sensor - Tou, Zhi Qiang (2014)
A biocompatible fiber-optic pH sensor based on a unique double-pass Mach–Zehnder interferometer is proposed. pH responsive poly(2-hydroxyethyl methacrylate-co-2-(dimethylamino)ethyl methacrylate) hydrogel coating on the fiber swells/deswells in response to local pH, leading to refractive index changes that manifest as shifting of interference dips in the optical spectrum. The pH sensor is tested in spiked phosphate buffer saline and demonstrates high sensitivity of 1.71  nm/pH , pH 0.004 limit of detection with good responsiveness, repeatability, and stability. The proposed sensor has been successfully applied in monitoring the media pH in cell culture experiments to investigate the relationship between pH and cancer cell growth.